Body posture self-assessment tools: a scoping review (Fisioterapia e Pesquisa, 2023)
Postural therapies use active treatmentmethods, such as self-correction, to control bodysegments. The evidence for this practice is establishedfrom the comparison of the self-perception of bodyposture before, during, and after postural education.A scoping review of tools to assess self-perception ofbody posture, besides encouraging research, may guideprofessionals while developing treatments. This scopingreview aims to identify the existing tools that assessself-perception of body posture, describing their type,measurement properties (validity and reliability),and postural outcomes. The protocol of this review wasregistered in the Open Science Framework (OSF), DOI:10.17605/OSF.IO/JGH8U. Studies developing and/orevaluating measurement properties and other studydesigns using self-perception of static body posture as anassessment method were included. In total, 359 studieswere found, of which six were analyzed in this study.They presented two types of tool and their measurementproperties were related to validity (n=6) and reliability(n=5). Five studies performed the joint analysis of validityand reliability (83%). Spine position, leg and foot posture,trunk and rib deformity, and postural awareness in generalwere the assessed postural outcomes. Of the six toolsthat assess self-perception of body posture, only the SSFS scale can be used in any population. To date, no studyfound a tool that assesses self-perception of body posture and considers all body segments